Strengthening Empowering Leadership Effects on Innovation: The Roles of Innovative Climate and Collaborative HRM (Study on East Java Patchwork and Quilting Craftsmen) - Irma Septia Ningsih (Proceeding Economy of Asia International Conference, 2026)
Introduction/Main Objectives: This study aims to strengthen theoretical and empirical understanding of how empowering leadership influences craftsmen’s innovative work behavior through the mediating role of organizational climate for innovation and the moderating role of collaborative human resource management systems (CHRMS). The research focuses on the Pelanusa Patchwork & Quilting community in East Java as a representative of Indonesia’s creative MSME sector. Background Problems: In the creative craft sector, the level of innovation remains low. Many artisans repeat existing designs without exploring new ideas due to limited leadership support, weak collaboration, and low confidence. Novelty: This paper introduces an integrated model combining empowering leadership, organizational climate for innovation, and collaborative HRM systems to explain the emergence of innovative work behavior in artisan communities. It expands previous theories by applying them to non-formal, community-based organizations, where innovation is shaped more by social interaction, trust, and shared ownership than by hierarchical structures. Research Methods: A quantitative methodology based on Partial Least Squares Structural Equation Modeling (PLS-SEM) was adopted to collect data from 199 craftsmen using validated survey instruments. The variables measured include EL, OCI, CHRMS, and CIWB. Finding/Results: The results show that empowering leadership significantly enhances innovative behavior through both direct pathways and indirect effects facilitated by OCI. Moreover, CHRMS positively moderates the relationship between EL and CIWB. The model demonstrates a high Goodness-of-Fit (GoF = 0.817), indicating strong explanatory power. Conclusion: Empowering leadership effectively fosters innovative behavior when supported by a collaborative HRM system and an innovation-oriented climate. The study contributes theoretically to HRM and leadership research and provides practical insights for MSME leaders and policymakers to strengthen innovation and sustainability in local artisan communities.